Manajemen Keuangan dan Pembiayaan di Madrasah - M.Yunus Anwar (Universitas Muslim Indonesia, 2022)
Financial management is one of the substances of school management that will also determine the running of educational activities in schools. As is the case in the substance of educational management in general, financial management activities are carried out through the process of planning, organizing, directing, coordinating, supervising or controlling.